KONSEP DIRI PEMILIH PEMULA SEBAGAI PARTISIPAN POLITIK PADA PEMILU LEGISLATIF APRIL 2014 (Studi Interaksi Simbolik pada Mahasiswa Prodi Ilmu Komunikasi, Universitas Bunda Mulia) - Lasmery RM Girsang (Universitas Bunda Mulia, 2014)
Everybody has different self concept, one another that was been created from long time. There are several processes to form a self-concept. A person's self-concept is the result of (process) long experience. In this case, the individual takes a long time to recognize him/herself. In process, a person may experience the 'ups and downs' in an attempt to understand life. That’s why Brooks (1974) said that self-concept as “those physical, social and psychological perceptions of ourselves that we have derived from experiences and our interactions with other”. In this research, researcher will seek self concept from students from communication department of UBM as participant (especially as young voters).This qualitative method uses “Symbolic Interactionism” from Blummer. Besides that, this research also tries to find out the factors that influence the student’s self concept. The results for self-concept are different from one respondent to other respondents. But their responds for symbolic interactionism are almost same. Finally, researcher makes two categories based on that results, namely “Active-Young Voter” and “Passive-Young Voter”. Keywords: Self Concept, Young Voter, Political Participant, Legislative Election, Symbolic Interactionism